Reconstructing one-stop student communities for study-abroad preparation in Chinese higher education: A qualitative case study - Jiang, Shuxian; Zhang, Yan; Shen, Hui (Journal of International Students, 2026)
As the internationalization of higher education continues to accelerate, universities are becoming increasingly challenged by the need to provide integrated support systems for students preparing for overseas study. Existing studies on one-stop student communities have focused mainly on domestic undergraduate management and have rarely examined how such communities support study-abroad preparation, intercultural adaptation, and long-term student development. Drawing on the three-all education framework, intercultural learning theory, and transformative learning theory, the study collected multisource qualitative data through semistructured interviews with 32 participants, document analysis, and eight weeks of onsite observation, which were analyzed using thematic analysis. The findings reveal three major dilemmas in the current one-stop student community model: insufficient multistakeholder collaboration, fragmented support across different stages of study-abroad preparation, and superficial implementation of all-around educational functions. The participants particularly emphasized the lack of psychological preparation, personalized intercultural guidance, and sustained overseas support.